До 150-річчя від дня народження Лесі Українки (1871–1913) - Dzyk, Roman (Yuriy Fedkovych Chernivtsi National University, 2021)
To the 150th Anniversary of Lesya Ukrainka
To the 150th Anniversary of Lesya Ukrainka (1871–1913)
Keywords: Lesya Ukrainka; Anniversary; Bibliography